Pneumonia among under-five children in Alexandria, Egypt: a case-control study - Noha Fadl; Ayat Ashour; Yasmine Yousry Muhammad (SpringerOpen, 2020)
Abstract Background Pneumonia among under-five children constitutes a major public health concern. Studies examining risk factors for pneumonia in Egypt are limited. Aim To identify risk factors of pneumonia among under-five children in Alexandria, Egypt. Methods An observational case-control study was conducted over a 5-month period (September 2017-January 2018) in three main pediatric hospitals in Alexandria. A predesigned questionnaire was used to interview 660 mothers of under-five children (330 pneumonia cases and 330 control). The questionnaire included potential risk factors for pneumonia which were categorized into child-related factors, socio-demographic factors, and environmental factors. Results The mean age of the children was 23.14 ± 18.61 months with a range of 1-59 months. Nearly two-thirds (58.5%) were boys. Nine factors were found to be independently associated with pneumonia: age ≤ 12 months (OR = 1.925; 95% CI, 1.356-2.733; P < 0.001), male gender (OR = 1.646; 95% CI, 1.162-2.332; P = 0.005), birth order ≥ 4 (OR = 2.154; 95% CI, 1.282-3.617; P = 0.004), low birth weight (OR = 2.562; 95% CI, 1.718-3.821; P < 0.001), prematurity (OR = 2.019; 95% CI, 1.154-3.531; P = 0.014), place of delivery either at home (OR = 5.669; 95% CI, 1.063-30.237; P = 0.042) or at a public hospital (OR = 1.616; 95% CI, 1.131-2.310; P = 0.008), presence of concomitant illness (OR = 1.902; 95% CI, 1.043-3.469; P = 0.036), poor home aeration (OR = 3.586; 95% CI, 1.971-6.522; P < 0.001), and exposure to outdoor air pollution (OR = 2.403; 95% CI, 1.417-4.076; P = 0.001). Conclusion Several risk factors were significantly related to pneumonia among under-five children. Identifying such factors is important for developing interventions to reduce pneumonia burden among under-five in Egypt.